Interstitial lung diseases associated with metal content in silicone breast implants: a case series - Fireman, Elizabeth; Rosengarten, Dror; Einat, Einat; Kramer, Mordechai R (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Silicone gel-filled breast implants have been widely used for breast augmentation and reconstruction since the 1960’s when the FDA approved them in women over 22 years of age. Concerns have been raised about the safety of those implants, with the focus upon whether silicone leak can spread to regional lymph nodes and remote organs and possibly cause inflammatory and immune responses. Objective: To present laboratory workup findings in 3 cases of interstitial lung diseases (ILD) linked with silicone implant leakage. Methods: ILD was diagnosed by tissue biopsy and Computerized Tomography (CT). We analyzed the metal content in both biological samples and raw material of the implants by means of scanning electron microscopy (SEM) and X-ray fluorescence (XRF). The metals lymphocyte proliferation analysis (MELISA®) was used to assess sensitization of the immune system to 19 metals. Results: The biological samples contained metals (silicon, nickel, zinc, tungsten, iron, aluminum, and zirconium) which are also present in the silicone implant. The MELISA test showed sensitization to nickel, zinc and tin. Limitations: Some of the immunogenic metals present in the implant were under the limits of detection of SEM and XRF and the sensitivity of MELISA test is unknown. Conclusions: The laboratory assessments of the 3 herein described women indicated that their interstitial lung disease was associated with the metal content of their silicone gel-filled breast implantations.